Hadith #415 - Al-Adab Al-Mufrad (Al-Adab Al-Mufrad)
Salim ibn ‘Abdullah reported from his father that ‘Umar used to say to his sons, “Separate in the morning and do not meet together in the same house. I fear that you might split up or that some evil may take place between you.”
Grade:

Hadith #416 - Al-Adab Al-Mufrad (Al-Adab Al-Mufrad)
Ibn ‘Umar saw a shepherd with some sheep in a bad place and saw a place which was better than it. He told him, “Woe to you, shepherd! Move them! I heard the Messenger of Allah, may Allah bless him and grant him peace, say, ‘Every shepherd is responsible for his flock.'”
Grade:

Hadith #417 - Al-Adab Al-Mufrad (Al-Adab Al-Mufrad)
Ibn ‘Abbas reported that the Prophet, may Allah bless him and grant him peace, said, “We do not give a bad example. The one who takes back his gift is like the dog who returns to his own vomit.”
Grade:

Hadith #418 - Al-Adab Al-Mufrad (Al-Adab Al-Mufrad)
Abu Hurayra reported that the Messenger of Allah, may Allah bless him and grant him peace, said, “The believer is guileless and generous while the corrupt is a swindler and miserly.”
Grade: